2021
DOI: 10.1038/s41598-021-91393-y
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic shift precedes the resolution of inflammation in a cohort of patients undergoing bariatric and metabolic surgery

Abstract: Bariatric and metabolic surgery has shown to promote weight loss and reduce systemic inflammation. However, the sequence and timing of events regarding metabolic improvement and inflammation resolution has been rarely explored. Furthermore, data on inflammatory markers of Th17 and Th1 cell responses after bariatric surgery is scarce. We conducted a prospective study in subjects with obesity that underwent bariatric and metabolic surgery, with follow-ups at 3 and 6 months. Anthropometric and metabolic markers s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 64 publications
0
25
0
Order By: Relevance
“…Seventy-two percent (26/36) of patients at 3 months achieved an excess weight loss (EBWL) ≥ 25% and 47% (17/36) succeeded ≥ 45% EBWL at 6 months ( Table 1 ). As bariatric surgery has shown an important impact on different inflammatory markers, 4 , 5 , 6 we also determined if bariatric surgery affected the accumulation of LDN in circulation as an indicator of improvement of inflammation. For this, we tested the effect of bariatric surgery on LDN in the peripheral blood of MOP in a prospective longitudinal study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventy-two percent (26/36) of patients at 3 months achieved an excess weight loss (EBWL) ≥ 25% and 47% (17/36) succeeded ≥ 45% EBWL at 6 months ( Table 1 ). As bariatric surgery has shown an important impact on different inflammatory markers, 4 , 5 , 6 we also determined if bariatric surgery affected the accumulation of LDN in circulation as an indicator of improvement of inflammation. For this, we tested the effect of bariatric surgery on LDN in the peripheral blood of MOP in a prospective longitudinal study.…”
Section: Resultsmentioning
confidence: 99%
“… 3 Also, recent studies have shown that bariatric surgery significantly reduces several inflammatory mediators such as cytokines, hormones, and acute phase reactants, 4 , 5 most likely as a result of the resolution of metabolic disturbances. 6 However, much less is known about inflammatory cells. Prior research has shown that different stages of adiposity (overweight, obesity, and severe obesity) favor the accumulation of myeloid cells including macrophages, 7 and neutrophils.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, metabolic parameters improved after bariatric surgery already after three months, whereas it took six months in the same cohort of patients to achieve a significant improvement in the body mass index and a reduction in the circulating pro-inflammatory cytokine levels, among others TNFα, IL-1β and IL-6 [ 157 ]. Notably, circulating MCP1 levels did not significantly decrease during the observation period in this study.…”
Section: Role Of Macrophages In the Development Of Insulin Resistance...mentioning
confidence: 99%
“…Overnutritioninduced adipocyte hypertrophy thereby promotes the development of insulin resistance, chronic inflammation, macrophage infiltration into the adipose tissue, mitochondrial dysfunction and ultimately adipocyte death [8,9]. These negative consequences of overnutrition are reversed by drastic reduction in food intake [6,10], as well as by bariatric surgery [8,[11][12][13][14], and are accompanied by a normalization of serum adiponectin levels [7,[10][11][12][13]. Consequently, hypoadiponectinemia is considered both a risk factor [15,16] and a biomarker [17][18][19] of type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%